Legal Status of the Accounting Chamber of Ukraine: Current State and Perspectives of Development (Law and Safety, 2021)
The bases of the legal status of the Accounting Chamber have been studied: rights, duties, responsibilities, principles, purpose, functions, place of the Accounting Chamber among other state agencies and their interaction. It has been emphasized that the Accounting Chamber should be assigned the status of the Supreme Audit Institution in order to harmonize the legal definition of the legal status of the Accounting Chamber with international standards, namely the Lima Declaration of Control Guidelines, which should assist in expanding the powers of the state agency and should facilitate the effective realization of control functions. The authors have studied the problem of compliance of the Accounting Chamber with the principle of independence contained in the Constitution of Ukraine and in the Law of Ukraine “On the Accounting Chamber”.The emphasis has been placed on the fact that the legislator identifies the legal categories of “state financial audit” and “state external financial control (audit)” in the Law of Ukraine “On the Accounting Chamber”, by using the phrase “state external financial control (audit)”. It is the basis for authors to emphasize the importance of adopting a regulatory act, which will be designed to distinguish between basic categories (concepts) in the field of public financial control (audit). The need to consolidate the functions of the Accounting Chamber at the legislative level and their delimitation with the powers of a state agency has been substantiated. The need to supplement the title of the Law of Ukraine “On the Accounting Chamber” with the word Ukraine has been emphasized.The shortcomings of the legal regulation of the institution of responsibility of officials of the Accounting Chamber have been highlighted. The emphasis has been placed on the fact that the mechanism for bringing officials of the Accounting Chamber to disciplinary responsibility is not regulated at a high level. The authors have emphasized on the improvement of normative and legal regulation of the special procedure for bringing guilty persons to administrative liability by authorized persons of the Accounting Chamber for violation of the law. Based on the analyzed experience of the Accounting Chamber of France, the authors have suggested the ways to improve the legal status of the Accounting Chamber of Ukraine.
Keywords: Accounting Chamber; legal status; Supreme Audit Institution; public financial control (audit); responsibility of the members of the Accounting Chamber.